A VIBRATIONAL DAMAGE MODEL FOR PEARS BASED ON FATIGUE ACCUMULATIVE DAMAGE THEORY - Chenxu Zhao; Yuchi Li; Xue Huang; Shujie Song (Engenharia Agrícola)
ABSTRACT Fatigue vibration is a primary cause of fruit damage during transportation. Drawing on the Palmgren–Miner fatigue accumulation damage theory and the correlation between fruit vibration damage characteristics and external vibration excitation, this paper proposes a fruit vibration fatigue accumulation damage model and its method for parameter determination. Using pears as the research objects, we conducted fatigue damage vibration and critical fatigue damage vibration tests under various conditions to determine the vibration fatigue constant of the pears. By utilizing the critical value of the damage area specified in the pear grading standard for premium grade, we derived the threshold acceleration value for pear damage. These findings serve as a technical foundation for advancing our understanding of fruit vibration fatigue damage mechanisms and guiding the development of cushioning packaging to protect fruit from vibrations.